Host insulin resistance caused by Porphyromonas gingivalis-review of recent progresses - Jia, Shuxian; Li, Xiaobing; Du, Qin (Frontiers in Cellular and Infection Microbiology, 2023)
Porphyromonas gingivalis (P. gingivalis) is a Gram-negative oral anaerobic bacterium that plays a key role in the pathogenesis of periodontitis. P. gingivalis expresses a variety of virulence factors that disrupt innate and adaptive immunity, allowing P. gingivalis to survive and multiply in the host and destroy periodontal tissue. In addition to periodontal disease, P.gingivalis is also associated with systemic diseases, of which insulin resistance is an important pathological basis. P. gingivalis causes a systemic inflammatory response, disrupts insulin signaling pathways, induces pancreatic β-cell hypofunction and reduced numbers, and causes decreased insulin sensitivity leading to insulin resistance (IR). In this paper, we systematically review the studies on the mechanism of insulin resistance induced by P. gingivalis, discuss the association between P. gingivalis and systemic diseases based on insulin resistance, and finally propose relevant therapeutic approaches. Overall, through a systematic review of the mechanisms related to systemic diseases caused by P. gingivalis through insulin resistance, we hope to provide new insights for future basic research and clinical interventions for related systemic diseases.